Memory complaints and cognitive performance in fibromyalgia and chronic pain: The key role of depression. Issue 3 (4th February 2021) - Castel, Antoni; Cascón‐Pereira, Rosalia; Boada, Sergi
Abstract : To explore the relationship between perceived cognitive problems and cognitive performance in three different samples, taking into account the possible influence of depression, catastrophizing, pain intensity, or medication. Seventy individuals with fibromyalgia, 74 with non‐malignant chronic pain and 40 pain‐free controls, completed measures of verbal episodic memory, sustained attention, response inhibition, depression, catastrophizing, and pain intensity. Fibromyalgia and chronic pain patients performed worse than controls in verbal memory and sustained attention, but these differences disappeared when depressed participants were excluded from the analyses. Memory complaints were related with depression in all pain patients. However, in the case of fibromyalgia, memory complaints were also related by pain intensity and inversely related by short‐term episodic memory. This case‐control study shows the importance of jointly assessing cognitive performance and memory complaints and of controlling for variables such as depression, catastrophizing, pain intensity and medication in the studied samples. Accordingly, this study highlights the differences in memory complaints, between the patients with fibromyalgia and the patients with other chronic pain conditions. Finally, it has highlighted the important role played by depression in cognitive performance and memory complaints considering the Neurocognitive Model of Attention to pain.